Genomic Structure and Comparative Analysis of Nine Fugu Genes: Conservation of Synteny with Human Chromosome Xp22.2–p22.1 - Brunner, Bodo; Todt, Tilman; Lenzner, Steffen; Stout, Karen; Schulz, Ute; Ropers, Hans-Hilger; Kalscheuer, Vera M. (Genome Research, 1999)
The pufferfish Fugu rubripes has a compact 400-Mb genome that is ∼7.5 times smaller than the human genome but contains a similar number of genes. Focusing on the distal short arm of the human X chromosome, we have studied the evolutionary conservation of gene orders in Fugu and man. Sequencing of 68 kb of Fugugenomic DNA identified nine genes in the following order: (SCML2)-STK9, XLRS1, PPEF-1, KELCH2, KELCH1, PHKA2, AP19, and U2AF1-RS2. Apart from an evolutionary inversion separatingAP19 and U2AF1-RS2 from PHKA2, gene orders are identical in Fugu and man, and all nine human homologs map to the Xp22 band. All Fugu genes were found to be smaller than their human counterparts, but gene structures were mostly identical. These data suggest that genomic sequencing in Fugu is a powerful and economical strategy to predict gene orders in the human genome and to elucidate the structure of human genes.[Sequence data for this article were deposited with the EMBL/GenBank data libraries under accession nos. AJ011381 and AF094327.]